The effects of controlled smoking on heart period variability. - Nabors-Oberg, R.E.
This article presents a study that examined the cardiovascular effects of a single session of repetitive cigarette smoking to investigate the possible development of short-term tolerance.
Keywords: Autonomic nervous system changes; Autoregressive spectra; Cardiac function; Cardiovascular disease; Cardiovascular effects; Continuous electrocardiogram measurements; Controlled smoking effects; Frequency-domain measures; Gender differences; Heart period variability; Nicotine tolerance; Nonlinear indices; Parasympathetic activity; Physiological time series; Quantified smoke delivery system; Repetitive cigarette smoking; Short-term tolerance; Spectral analysis; Vagal modulation